The role of custom in determining the provisions of Islamic financial transactions - Mazlan, Nur Adleen Maisarah; Mohamad Razi, Nur Alieya Maisarah; Mat Nazin, Nur Hanan; Mohlis, Nurizzati Eliyana; Zawawi @ Mokhtar, Nurul ‘Izzah; Wan Sukiman, Wan Dalila Akmal (2024)
Custom plays an important role in determining the rules for financial transactions in Islam. It serves as an indirect source for understanding and applying Islamic legal texts in matters where there is no specific text, or for interpreting texts in accordance with prevailing customs, provided that custom does not contradict definitive texts. Custom is used to interpret contracts, adapt new transactions, and fill legislative gaps, provided it is clear, stable, and consistent with the principles of justice. Examples of this include determining workers' wages or delivery deadlines in sales based on custom, or regulating modern contracts such as bank credits in accordance with Sharia regulations.